Penggunaan Figma dan Metode Design Thinking dalam User Interface dan User Experience untuk Website E-Commerce Pasar Grosir Tradisional - Erik, Muhammad; Wiranata, Ade Davy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to design the User Interface (UI) and User Experience (UX) of a management website for a wholesale store UD. Putra Banjar in Jakarta using Figma software and the Design Thinking method. The background of this study is the need for digitalization in stock and transaction management which has so far been done manually and is considered inefficient. This study identified four main problems: the integration of Figma and Design Thinking in the design process, the involvement of owners and customers in development, increasing transaction efficiency through the website, and providing additional features to increase customer trust in the product. The Design Thinking method used includes five stages, namely Empathize, Define, Ideate, Prototype, and Test. The initial stage is carried out through interviews with owners and customers to explore needs and problems. The results of the analysis are then formulated into a design solution that is visualized in the form of a prototype using Figma. Trials were carried out by 15 users to obtain feedback to improve the design. The expected results of this study are the creation of an effective, efficient, and responsive website UI/UX design to user needs. In addition, the product review feature is expected to help customers in decision making. This research is expected to contribute to the operational efficiency of UD. Putra Banjar and become a reference in the digitalization of similar MSMEs in Indonesia.